Implementation of Online Registration Information Technology in Health Service Delivery at Matur Primary Health Center in 2025 - Novelita Harlin; Silvia Adi Putri; Legabina Adzkia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2025)
Introduction: The utilization of information technology in the healthcare sector, such as the use of online registration at community health centers (puskesmas), presents an alternative healthcare service to avoid long queues. Through the online registration system, it is expected to enhance efficiency, accessibility, and service quality at primary healthcare facilities like puskesmas. Objective: This study aims to identify the 'man' (behavior/human resources), 'material' (infrastructure), and 'method' (procedural regulations/workflow) aspects in the implementation of online registration at Puskesmas Matur. Methods: This research was conducted from April 22nd to May 6th, 2025, using a qualitative descriptive approach involving five informants, namely officers and patients at Puskesmas Matur. Results: The research findings indicate a significant change in the service flow and interactions between patients and officers. The majority of patients expressed satisfaction with the use of online registration. However, some patients, particularly the elderly and those unfamiliar with using online registration, still face challenges. Registration officers stated that socialization regarding this system has been carried out, but further efforts are needed to reach all segments of society. Conclusion: The implementation of the online registration system at Puskesmas Matur has been generally received positively by both patients and healthcare officers. Patients perceive ease and flexibility in the registration process, although some patients still encounter technical difficulties, and further socialization efforts are deemed necessary. Keywords: Implementation, Information Technology, Online Registration